2023
DOI: 10.1037/bul0000391
|View full text |Cite
|
Sign up to set email alerts
|

Child maltreatment and alexithymia: A meta-analytic review.

Abstract: Alexithymia refers to difficulties identifying and describing one's emotions. Growing evidence suggests that alexithymia is a key transdiagnostic risk factor. Despite its clinical importance, the etiology of alexithymia is largely unknown. The present study employs meta-analytic methods to summarize findings on the role of one hypothesized antecedent of adult alexithymia, namely child maltreatment. We obtained effect size estimates from 99 independent samples reported in 78 unique sources that reported both ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0
2

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 201 publications
1
13
0
2
Order By: Relevance
“…Our current work also revealed an association of childhood trauma, mediated through alexithymia, with FI-DMN function in those who smoked nicotine. Specifically, more reported childhood trauma was associated with greater alexithymia, replicating previous work . However, no direct association was evident between the CTQ score and time in any brain state.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Our current work also revealed an association of childhood trauma, mediated through alexithymia, with FI-DMN function in those who smoked nicotine. Specifically, more reported childhood trauma was associated with greater alexithymia, replicating previous work . However, no direct association was evident between the CTQ score and time in any brain state.…”
Section: Discussionsupporting
confidence: 80%
“…Specifically, more reported childhood trauma was associated with greater alexithymia, replicating previous work. 26 However, no direct association was evident between the CTQ score and time in any brain state. Only through the association of childhood trauma with alexithymia did we find an association with neurobiological changes in individuals who smoked nicotine, indicating that it was the expression of symptoms such as alexithymia and not just trauma that was associated with FI-DMN dynamics.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Studies have shown that when compared to individuals without a history of maltreatment, victims of childhood maltreatment report higher levels of alexithymia 20 . Based on Ditzer et al’s meta-analysis 21 , children growing up in abusive environments such as those characterized by maltreatment do not properly learn to regulate their emotions or tolerate negative affects. They also lack modeling and reinforcement of appropriate coping strategies and emotional expressivity 20 , 22 .…”
Section: Introductionmentioning
confidence: 99%
“…According to the self-determination theory [ 24 ], parental psychological control has been linked to the development of alexithymia, often exacerbated by elevated instances of child maltreatment [ 25 ] and parental overprotection [ 26 ], and anxious attachment [ 20 , 27 ], as well as a reduction in psychological needs and the disruption of self-regulation [ 28 ]. Moreover, parents with alexithymic traits were found to show more parental psychological control, and may encounter challenges in comprehending their children’s emotional experiences [ 14 ].…”
Section: Introductionmentioning
confidence: 99%